Martian environmental chamber: Dust system injection. (1st October 2020) - Cozzolino, F.; Mennella, V.; Ruggeri, A.C.; Mongelluzzo, G.; Franzese, G.; Popa, C.I.; Molfese, C.; Esposito, F.; Porto, C.; Scaccabarozzi, D.
Abstract: The aim of this work is to describe the development and implementation of an experimental setup able to reproduce some characteristics of the Martian atmosphere. The development of such setup fits into the context of MicroMED project, that foresees the development of an optical particle counter to be accommodated on the ExoMars 2020 Surface Platform, as part of the suite of sensors named Dust Complex. MicroMED will perform the first direct measurement of the size distribution of the powder close to Martian surface. The experimental setup is able to reproduce the characteristics of the Martian atmosphere: pressure, atmospheric composition, the actual temperature in which MicroMED will operate (from −20 °C to 40 °C) and the most important thing: the presence of suspended dust . The main result obtained in this work was the right configuration of an experimental setup in which to test sensors or instruments that work in Martian conditions. In particular, a dust injection system has been developed in order to obtain a dust distribution that was localized and without the formation of particles aggregates, for a correct calibration of the instrument. Highlights: Having developed an experimental setup capable of reproducing some Martian weather conditions like atmospheric composition, presence of dust and pressure. Having developed a functional powder injection system for the calibration of a Martian optical particle counter. Use of ethanol to minimize the triboelectric effects of the grains injected into the simulation chamber and consequently to have drastically reduced the formation of dust aggregates. Possibility of injecting powder in different ways according to the needs. Tests on the first breadboard version of an optical particles counter capable of operating in Martian weather conditions.